The use of AVF.SIM system for the surgical planning of arteriovenous fistulae in routine clinical practice - Bozzetto, Michela; Poloni, Sofia; Caroli, Anna; Curtò, Diego; D’Haeninck, Annick; Vanommeslaeghe, Floris; Gjorgjievski, Nikola; Remuzzi, Andrea (SAGE Publications, 2022)
Background: The number of patients treated with hemodialysis (HD) in Europe is more than half a million and this number increases annually. The arteriovenous fistula (AVF) is the vascular access (VA) of first choice, but the clinical outcome is still poor. A consistent number of AVFs fails to reach the desired blood flow rate for HD treatment, while some have too high flow and risk for cardiac complications. Despite the skill of the surgeons and the possibility to use Ultrasound investigation for mapping arm vasculature, it is still not possible to predict the blood flow volume that will be obtained after AVF maturation. Methods: We evaluated the potential of using a computational model (AVF.SIM) to predict the blood flow volume that will be achieved after AVF maturation, within a multicenter international clinical investigation aimed at assessing AVF.SIM predictive power. The study population included 231 patients, with data on AVF maturation in 124 patients, and on long-term primary patency in 180 patients. Results: At 1 year of follow-up, about 60% of AVFs were still patent, with comparable primary patency in proximal and distal anastomosis. The correlation between predicted and measured blood flow volume in the brachial artery at 40 days after surgery was statistically significant, with an overall correlation coefficient of 0.58 ( p < 0.001). The percent difference between measured and predicted brachial blood flow 40 days after surgery was less than 30% in 72% of patients investigated. Conclusions: The results indicate that the use of the AVF.SIM system allowed to predict with a good accuracy the blood flow volume achievable after VA maturation, for a given location and type of anastomosis. This information may help in AVF surgical planning, reducing the AVFs with too low or too high blood flow, thus improving AVF patency rate and clinical outcome of renal replacement therapy.